A MANAGED MEDIATION IN RESOLVING DISPUTERS HOSPITAL HEALTH SERVICES - Mahzul Harahap; Redyanto Sidi (INFOKUM, 2022)
The relationship between medical personnel and the patient in carrying out their services as health workers is not uncommon with events where health workers ignore a patient's rights until a problem or dispute arises. Mediation is one of the means in alternative dispute resolution outside the court. The regulation regarding the settlement of disputes through mediation is regulated in Article 29 of Law Number 36 of 2009, where the article regulates mediation but does not clearly explain what mediation means, more specifically it is not explained about mediation efforts which result in implicit in its regulation, so it needs to be researched. The research method used in this research is normative juridical research method where this is done by researching library materials or what is often said with secondary data in the form of positive law. The results of this discussion show that in the event of a dispute, the dispute can be resolved.